To Feed or Not to Feed? Coral Reef Fish Responses to Artificial Feeding and Stakeholder Perceptions in the Aitutaki Lagoon, Cook Islands - Prinz, Natalie; Story, Richard; Lyon, Stephen; Ferse, Sebastian C. A.; Bejarano, Sonia (Frontiers in Marine Science, 2020)
Feeding wild animals is a regular habit in ecotourism worldwide with poorly known consequences for ecosystem functioning. This study investigates how effective is bread feeding at attracting coral reef fish in the South Pacific, which feeding groups of fish are most attracted, and how are natural foraging rates of an omnivorous and a grazing-detritivorous fish affected. Data were collected at sites where fish are regularly fed bread by snorkellers and at comparison sites where bread was only provided for this study, within the Aitutaki lagoon (Cook Islands). The fish community was censused and foraging rates of two model species (Chaetodon auriga, Ctenochaetus striatus) were quantified one hour before, during, and an hour after feeding events. Twenty-five percent of the species present at all sites (piscivores-invertivores) were effectively attracted to bread. Overall, mean fish density was higher at tourism feeding sites than at the comparison sites. During bread feeding events, taxonomic richness decreased, compared to the hours prior and after feeding across all sites. As piscivore-invertivores were consistently attracted to bread, localised shifts in their dominance over other trophic groups may be expected if bread feeding persists, likely carrying consequences for ecosystem functioning. The effect of bread feeding events on natural foraging rates differed between the model species. C. auriga ceased foraging on natural foods to feed on bread. Although C. striatus never fed on bread, its foraging rate on epilithic algal matrices decreased during bread feeding events. This indirect non-lethal ecological consequence of bread feeding contributes a previously unanticipated example relevant to the “ecology of fear” in marine fish. Stakeholder interviews revealed that locals favour feeding to sustain tourist satisfaction, whereas tourists appreciate snorkelling regardless of feeding. This indicates an opportunity for restrictions on fish feeding without drawbacks on tourism. Future research on fish metabolism and cascading effects on the reef benthos may reveal further impacts of feeding on coral reef communities.